Citizen Bardolph refused Admittance at Prince Hal's. - (:unkn) unknown (Humphrey, H., 1794)
Scholarly notes may be added at a later date.
1 print : b&w
Keywords: Caricatures; Cartoons; Drury Lane Theatre